The Problem of Designing Students' Creative Activities by Means of Pragmatic Exercises in Mother Language Education - Zokirov Javohir Gaybullo ugli (Journal of Higher Education and Academic Advancement, 2024)
In the article, the idea to justify the practice of designing students' creative activity in mother language education, to define its specific features, to determine the subject, purpose, and tasks of the pedagogical experiment, to describe the course of the experiment, and to analyze its results is presented. The main goal of designing students' creative activities in mother language education is to increase the effectiveness and quality of education. When and under what conditions the design of students' creative activities in mother language education gives the desired pedagogical effect? Answering this question requires a cross-sectional analysis of different types of education, including expository and creative education.